A study design and maintenance of facade for government building, Putrajaya / Sahrizan Ahmad - Ahmad, Sahrizan (Faculty Architecture, Planninng and Surveying, 2014)
Building design that takes into consideration aspect of maintenance during the design phase, it affects the performance of the building when it is fully operational. In Malaysia, for example, most of the designer of the building, especially the architect and design engineer claims they have sufficient experience in the field of maintenance, but the majority still not equally concerned with the maintenance aspect during a building designed. The aim of this study is to identify maintenance problems for external building facade, especially problematic from the failure of design, lack of information, the impact of design on maintenance activities. The objective of study is to study the relationship between the design and maintenance of building facade government building Putrajaya, to investigate maintenance problems for building facade and to improve guideline in maintnenance programme for building facade. The methodology on doing this dissertation that carry out by literature review, data collection, by questionnaire, interview and observation. The results showed, the main problem that the maintenance firms are currently facing that caused by building design. Problems in terms of maintenance access, maintenance management, equipment, problems to access all parts of the building's facade. In general, based on the result that have been collected and analysed, the structure of the facade is an essential part as well as aesthetic of the building one building organization, based on studies that have been conducted facade design and maintenance activities are related to each other and problem arise when there is an imbalance consideration of the desing and maintenance for the future. Based on a study conducted, building in putrajaya have a problems in term of design and maintenance activities on the facade of the structure is still in moderate. Thus, it is important for the management of a project concerned with issues regarding the maintenance from the beginning again to reduce the problems mentioned above.